Serial entrepreneurship and digital innovation - Cheng, Z.; Jarrar, H.; Pereira, R.; Salloum, C. (International Journal of Technology Transfer and Commercialisation, 2025)
Drawing on an eight-year longitudinal case of a Chinese 3D-software serial entrepreneur, this study examine how digital business-model innovation unfolds in practice. Through in-depth interviews, observations, and archival data, we trace key entrepreneurial events and their ties to digital-technology adoption. Findings show that such innovation is largely incremental, driven by iterative learning and adaptive routines that let ventures leverage existing capabilities while integrating emerging technologies to reshape value creation, proposition, and capture. The study extends dynamic-capabilities theory to resource-scarce, fast-evolving software ventures and offers actionable guidance for entrepreneurs navigating digital transformation. While limited to a single case, the insights invite multi-case and quantitative validation.